Strong magnetochiral dichroism of helical structures of garnet particles - A. Christofi; N. Stefanou (Optics Letters, 2013)
We report on the occurrence of strong nonreciprocal magnetochiral dichroism in helical structures of magnetic garnet spheres, which emerges as a result of the simultaneous lack of time-reversal and space-inversion symmetries, by means of rigorous full-electrodynamic calculations using the layer-multiple-scattering method. It is shown that a strong effect appears in flat band regions associated with enhanced natural and magnetic optical activity.